Integrin α5 subunit is required for the tumor supportive role of fibroblasts in colorectal adenocarcinoma and serves as a potential stroma prognostic marker. Issue 12 (6th November 2019) - Lu, Ling; Xie, Ruting; Wei, Rong; Cai, Chunmiao; Bi, Dexi; Yin, Dingzi; Liu, Hu; Zheng, Jiayi; Zhang, Youhua; Song, Feifei; Gao, Yaohui; Tan, Linhua; et al.
Abstract : The tumorigenesis of colorectal cancer (CRC) is a complicated process, involving interactions between cancer cells and the microenvironment. The role of α5 integrin subunit in CRC remains controversial, and previous studies mainly focused on cancer cells. Herein, we report an important role of α5 in stroma fibroblasts in the tumorigenesis of CRC. The expression of α5 was found to be located in colorectal tumor stroma rather than in epithelia cancer cells. Immunofluorescence colocalization and gene correlation analysis confirmed that α5 was mainly expressed in cancer‐associated fibroblasts (CAFs). Moreover, experimental evidence showed that α5 expression was required for the tumor‐promoting effect of fibroblast cells. In an in   vivo xenograft nude mice model, α5 depletion in fibroblasts dramatically suppressed fibroblast‐induced tumor growth. In an in   vitro cell coculture assay, α5 depletion or knockdown reduced the ability of fibroblasts to promote cancer cell migration and invasion compared with wild‐type fibroblasts; moreover, we observed that the expression and assembly of fibronectin were downregulated after α5 depletion or knockdown in fibroblasts. Analysis of the RNA‐Seq data of the Cancer Genome Atlas cohort revealed that high expression of ITGA5 (α5 integrin subunit) was correlated with poor overall survival in colorectal adenocarcinoma, which was further confirmed by immunohistochemistry in an independent cohort of 355 patients. Thus, our study identifies α5 integrin subunit as a novel stroma molecular marker for colorectal adenocarcinoma, offers a fresh insight into colorectal adenocarcinoma progression, and shows that α5 expression in stroma fibroblasts underlies its ability to promote the tumorigenesis of colorectal adenocarcinoma. Abstract : The role of α5 integrin subunit in colorectal cancer (CRC) remains controversial. Here, we report an important role of α5 in stroma fibroblasts in the tumorigenesis of CRC, which might be mediated by affecting fibronectin expression and assembly. Clinically, our study showed that α5 expression was associated with overall survival in colorectal adenocarcinoma, and was positively correlated with fibronectin expression.